The Role of Nicotinamide in Cancer Chemoprevention and Therapy - Nikas, Ilias P. (Biomolecules, 2020)
Nicotinamide (NAM) is a water-soluble form of Vitamin B3 (niacin) and a precursor of nicotinamide-adenine dinucleotide (NAD(+)) which regulates cellular energy metabolism. Except for its role in the production of adenosine triphosphate (ATP), NAD(+) acts as a substrate for several enzymes including sirtuin 1 (SIRT1) and poly ADP-ribose polymerase 1 (PARP1). Notably, NAM is an inhibitor of both SIRT1 and PARP1. Accumulating evidence suggests that NAM plays a role in cancer prevention and therapy. Phase III clinical trials have confirmed its clinical efficacy for non-melanoma skin cancer chemoprevention or as an adjunct to radiotherapy against head and neck, laryngeal, and urinary bladder cancers. Evidence for other cancers has mostly been collected through preclinical research and, in its majority, is not yet evidence-based. NAM has potential as a safe, well-tolerated, and cost-effective agent to be used in cancer chemoprevention and therapy. However, more preclinical studies and clinical trials are needed to fully unravel its value.